Abnormal Cerebrovascular Reactivity and Functional Connectivity Caused by White Matter Hyperintensity Contribute to Cognitive Decline - Yang, Dan; Qin, Ruomeng; Chu, Lan; Xu, Hengheng; Ni, Ling; Ma, Junyi; Shao, Pengfei; Huang, Lili; Zhang, Bing; Zhang, Meijuan; Xu, Yun (Frontiers in Neuroscience, 2022)
Aims: To investigate the relationships of impaired cerebrovascular reactivity (CVR) and abnormal functional connectivity (FC) with white matter hyperintensity (WMH) related cognitive decline. Methods: A total of 233 WMH subjects were recruited and categorized into WMH-I (n=106), WMH-II (n=72) and WMH-III (n=55) groups according to Fazekas rating scale. All participants underwent neuropsychological tests and multimodal MRI scans, including 3D-T1, and resting-state functional magnetic resonance imaging (rs-fMRI). The alterations of CVR map and functional connectivity were further explored. Results: Subjects with a higher WMH burden displayed lower CVR in left medial occipital gyrus (MOG). FC analysis using MOG as a seed revealed that FC of left insula, left inferior parietal lobule (IPL), and thalamus changed abnormally as WMH aggravated. After adjusting for aging, gender, and education years, serial mediation analysis revealed periventricular white matter hyperintensity (PWMH) contribute indirectly to poorer Mini-Mental State Examination (MMSE) (Indirect effect: β=-0.1248, 95% CI [-0.4689, -0188]), poorer Montreal Cognitive Assessment (MoCA) (Indirect effect: β=-0.1436, 95% CI [-0.4584, -0.0292]) scores, and longer TMT-A (Indirect effect: β=0.1837, 95% CI [0.0069, 0.8273]) times, specifically due to lower CVR of left MOG and higher FC of left insula-MOG. Conclusion: The CVR decline of left MOG and abnormal FC of left insula-MOG attributed to WMH progression were responsible for poor general cognition (MMSE &MoCA) and information processing speed (TMT-A). Left MOG may act as a connection, which involved in the processing of cognitive biases by connected with left insula-cortical regions in WMH individuals. Keywords: white matter hyperintensity; cognitive decline; cerebrovascular reactivity; functional connectivity, rs-fMRI